Strengthening Youth Roles in Environmental Management: A CBR Approach to Compost Production and Waste Banking in Bendungan Village - Ahmad Fahrudin; Fahmi Muhamad; Adetokunboh Abayomi Adepoju (Kerigan: Jurnal Pengabdian Masyarakat, 2025)
Purpose: The purpose of this service activity is to empower adolescents in Bendungan Village, Gondang District, Tulungagung Regency, through training in making compost and management of garbage banks based on Community-Based Research (CBR) approaches. The main problem raised is the lack of awareness and skills of adolescents in managing waste independently and sustainably. Method: The method used in this activity is a participatory approach through CBR, which involves adolescents as active subjects in program planning, implementation, and evaluation. The stages of activities include identification of needs, environmental counseling, technical training in making compost, assistance in the management of waste banks, as well as monitoring and evaluation based on community involvement. Practical Applications: This activity has a significant practical application, including increasing the capacity of adolescents in managing organic waste, the formation of clean and environmentally friendly living habits, as well as the economic potential of the use of compost and the results of waste management. In addition, this activity also encourages the active participation of the community in maintaining the environment in a sustainable manner. Conclusion: The results of dedication show that this training is able to increase adolescent awareness and skills in waste management, as well as strengthen their role as agents of change in the village environment. The success of this program confirms that the CBR approach is effective in increasing the independence and social responsibility of the community, especially the younger generation.